Indigenous Media and Political Imaginaries in Contemporary Bolivia - Zamorano, Gabriela (Book collections on Project MUSE., 2017)
"Gabriela Zamorano Villarreal examines the political dimension of indigenous media production and distribution as a means by which indigenous organizations articulate new claims on national politics in Bolivia, a country experiencing one of the most notable cases of social mobilization and indigenous-based constitutional transformation in contemporary Latin America. Based on fieldwork in Bolivia from 2005 to 2007, Zamorano Villarreal details how grassroots indigenous media production has been instrumental to indigenous political demands for a Constituent Assembly and for implementing the new Constitution within Evo Morales controversial administration."--Provided by publisher.